RENGHUB: MEMPERBARUI BANGUNAN MATI FUNGSI DI AREA MRT LEBAK BULUS GRAB - Ayala Jayanegara Widjanarko; J.M. Joko Priyono Santoso (Jurusan Arsitektur dan Perencanaan, 2023)
The construction of the flyover and Lebak Bulus Grab MRT Station, along the Jakarta-Bogor street, South Jakarta, has had an impact in the form of the death of trade and other activities (the Friday market area, football community, and the Lebak Bulus bus transit area), especially around the station area. MRT. Physical deterioration and activity on these sections must be injected with activity in the hope of being able to restore the dynamics of life, such as building Renghub. Aims to update the function of a dead building. The method used is descriptive qualitative by making direct observations in the field. Data can be obtained by utilizing what is already there (secondary data) and searching for new data (primary data). The results achieved are in the form of interaction activities between MRT users and other means of transportation, which are accommodated in a building with the characteristics of the past, Lebak Bulus and Friday markets. The results achieved still require development in other sectors which in the end can synergize with Renghub, and be able to restore environmental dynamics to the way they were before. Keywords: MRT; mass rapid transit; death of activities; deterioration; update the function Abstrak Pembangunan jalan layang dan Stasiun MRT Lebak Bulus Grab, di sepanjang jalan Jakarta-Bogor Lebak Bulus, Jakarta Selatan, memberikan dampak dalam bentuk matinya aktivitas perdagangan dan aktivitas lain (area pasar jumat, komunitas bola, dan area transit bus Lebak Bulus) khususnya di sekitar area stasiun MRT. Disebabkan terjadinya degradasi fisik dan aktivitas pada ruas tersebut maka harus disuntikan program dengan harapan mampu mengembalikan dinamika kehidupan, seperti membangun Renghub. Bertujuan untuk memperbaiki fungsi bangunan yang sudah mati. Metode yang digunakan adalah deskriptif kualitatif dengan menyandingkan antara data dan konsep Urban Acupuncture. Data dapat diperoleh dengan melakukan pengamatan di lapangan secara langsung, apa yang sudah ada (data sekunder) dan pencarian data baru (data primer). Hasil yang dicapai dalam bentuk aktivitas interaksi antar pengguna MRT dan alat transportasi lain, yang ditampung dalam sebuah bangunan dengan karakter masa lalu Lebak Bulus dan Pasar Jumat dengan memasukan konsep arsitektur berkelanjutan. Untuk mencapai hasil yang sempurna masih diperlukan pengembangan pada sektor-sektor lain yang pada akhirnya dapat bersinergi dengan Renghub, dan mampu mengembalikan dinamika lingkungan yang berkembang.